2013
DOI: 10.3109/21681805.2013.788552
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a marker for evaluation of treatment effect of cyclosporine A in patients with bladder pain syndrome/interstitial cystitis type 3C

Abstract: The results indicate that measurement of NO is a tool for evaluating the response to anti-inflammatory treatment in patients with BPS/IC type 3C. NO could serve as a marker for assessing the activity of the inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…[95][96][97][98] Patients with Hunner's lesions seem to derive a better response than those without Hunner's lesions (68% vs. 30%, respectively). 96 A single RCT comparing CyA to PPS showed a significant improvement in IC/BPS symptoms with CyA treatment compared to PPS (59% vs. 13%, p<0.001).…”
Section: Cyclosporine a (Cya) (Option As A Last Resort In Patients Wimentioning
confidence: 94%
“…[95][96][97][98] Patients with Hunner's lesions seem to derive a better response than those without Hunner's lesions (68% vs. 30%, respectively). 96 A single RCT comparing CyA to PPS showed a significant improvement in IC/BPS symptoms with CyA treatment compared to PPS (59% vs. 13%, p<0.001).…”
Section: Cyclosporine a (Cya) (Option As A Last Resort In Patients Wimentioning
confidence: 94%
“…Six studies used the NIDDK criteria for diagnosing IC (12,14,(16)(17)(18); the other two studies used clinical symptoms to diagnose PBS/IC (11,13). The subjects of two studies (13,14) were patients in whom multiple first line therapies had failed.…”
Section: Resultsmentioning
confidence: 98%
“…Eight articles (11)(12)(13)(14)(15)(16)(17)(18) were finally included as eligible articles, which including a total of 298 subjects with a median number of 37.25 subjects per study. These 8 studies included 3 RCTs (16)(17)(18), 4 prospective cohort studies (11)(12)(13)15) and 1 retrospective cohort study (14). In the 7 studies that reported the ages of the subjects, the age predilection was 40-70 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations